ANALISIS DAN DESAIN SISTEM INFORMASI AKUNTANSI ASET TETAP PADA HOTEL G SUITES SURABAYA - Effendy, Jessica Novia; Widyaningdyah, Agnes Utari (Widya Mandala Surabaya Catholic University, 2016)
This research is a case study of designing and analyzing about accounting information systems of fixed asset. Currently, the tourism sector as an economic activity has become a priority for the development of a number of countries. The tourism sector in Indonesia is increasingly growing, and it is spurring growth of hotel in Indonesia. Therefore, this research is about improve the accounting information systems of fixed asset in a hotel. The object of this research is Hotel G Suites Surabaya. The scope of this research is limited to the accounting information system of fixed asset that consists of acquisition cycle, maintenance cycle, and the termination cycle of fixed assets. The methods of this research are observation, interview, and documentation. The hotel has prob-lems such as loss of goods in the hotel rooms and restaurant. The hotel doesn’t have maintenance procedure and termination pro-cedure of fixed assets, even though the procedure is very important for the hotel to reduce the risk of loss of fixed assets due to errors procedure. Hotel has implemented internal control. Internal control of the hotel still has deficiency. Hotel G Suites Surabaya needs to fix the job description, organizational structure, the design of documents, use the asset number for fixed assets and the serial number for document, and also fix the purchase procedure of fixed.